The Effect Of Poverty, Cigarette Prices, And Cigarette Production On Cigarette Consumption In East Java Province - Zulditia, Elo; Nilasari, Aprilia (Independent: Journal of Economics, 2024)
This study aims to determine the effect of poverty, cigarette prices, and cigarette production on cigarette consumption in East Java Province. The data used in this study were obtained from BPS, Worldbank, and the Directorate General of Plantation with a span of 4 years starting in 2019-2022. This study uses panel data regression analysis and the results obtained are Poverty, Cigarette Prices have a positive effect on Cigarette Consumption. While Cigarette Production has no effect on Cigarette Consumption. And together Poverty, Cigarette Prices and Cigarette Production affect Cigarette Consumption